Patients' anxiety and its causes in the pre-operative period - Buivydienė, Agnė; Jakavonytė-Akstinienė, Agnė (Slauga. Mokslas ir praktika, 2023)
Anxiety is usually caused by even minor surgery.  The necessity of the procedure, the high pre-operative emotional arousal, the post-operative pain, the difficult and lengthy recovery process, the hospital environment, the diagnostic and preparatory tests, the attending and nursing staff-these are all factors that can influence the pre-operative anxiety a patient feels.The aim of this study is to analyse the anxiety and its causes in the preoperative period.Methods. A quantitative study was conducted.Results and conclusions the sample was random. 110 respondents participated in the study. The respondents often felt anxiety in the preoperative period, which was caused by intrusive thoughts about the surgery, the length of the postoperative period and the pain of the disease. In contrast, factors such as possible drug allergy, lack of information and negative postoperative outcomes were seen as minor contributors to anxiety. It was observed that the respondents were less likely to experience physical symptoms of anxiety. In contrast, psychological symptoms were more frequent in the preoperative period. Although the vast majority of respondents stated that they did not need psychological support, the study showed that some respondents tended to communicate actively with both relatives and nurses.
Keywords: anxiety; patients; pre-operative period